The significance of higher vocational trainings with students’ eyes - Horváthné Tóth, Ildikó; Tóth, Katalin (Acta Scientiarum Socialium, 2012)
The significance of higher vocational trainings with students’ eyes In The National Qualifications Register (NQR), individuals who wanted to learn can choose from many higher vocational trainings. As preliminary training the acquisition of final exam is enough. Higher vocational trainings can be advertised in higher edu-cational institutions, secondary schools consisting in an agreement, vocational and adult educational institutions and companies. Many entrance examiners chose this training, in one respect they obtain profession, on the other hand, they get extra point to pass into any university or college. The higher vocational education, however, is facing with new changes this year. In our presentation, we examined at Kaposvar University Faculty of Education the launched and ongoing post-secondary vocational trainings both for full and part time students, their related future ideas and the opportunities of proceeding with the qualification.